2010
DOI: 10.1111/j.1600-0684.2009.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of daily repeated sedation using ketamine or ketamine combined with medetomidine on physiology and anesthetic characteristics in Rhesus Macaques

Abstract: These findings demonstrate repeated anesthesia with ketamine can initiate changes suggesting a tolerance effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 8 publications
7
18
0
Order By: Relevance
“…In addition, as described in other studies [32,35], a combination of medetomide and ketamine provides more muscle relaxation than ketamine alone.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, as described in other studies [32,35], a combination of medetomide and ketamine provides more muscle relaxation than ketamine alone.…”
Section: Discussionsupporting
confidence: 54%
“…However, retching and vomiting were not seen in macaques given ketamine-medetomidine [35]. The observed retching and vomiting during recovery, could also be due atipamezole, however, no information is available about the side effects of atipamezole in primates [28-30,32-35]. …”
Section: Discussionmentioning
confidence: 99%
“…Other authors have suggested that the benzodiazepines reduce rates of glomerular filtration and urine production in humans, so that these changes in electrolytes could be related to the use of the tranquilizers and sedatives applied in this study. It is important to emphasize that while our results reveal significant differences among the different anesthetic mixtures compared to controls, they remained within the ranges of normality published previously …”
Section: Discussionsupporting
confidence: 85%
“…In addition, this has been shown to decrease the number of respirations per minute by depressing the respiratory centers of the CNS, findings that are consistent with the reduction in SpO 2 observed in Group 5 . According to Settle et al, depression of the HR due to administration of xylazine can be attributed to the combined action of the baroreceptor reflex and vasoconstriction mediated by the α2 receptor. The vasopressor effect of the α2 adrenoceptors produces greater vagal activity while inhibiting central sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of this approach is the ability to maintain normal physiology. Important drawbacks include sedative medication side effects, the stress of anaesthesia and lack of flexibility in sampling times 25 . An alternate approach involves training NHPs, for example using the Positive Reinforcement Technique, to present themselves for sampling.…”
Section: Discussionmentioning
confidence: 99%